2021
DOI: 10.2139/ssrn.3905065
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects of the Covid-19 Pandemic on Entrepreneurship and Small Businesses

Abstract: but also creating productive entrepreneurship and resilient location-specific entrepreneurial ecosystems. The COVID-19 pandemic is an unprecedented challenge for small businesses that also brings new market opportunities. The papers in this special issue of Small Business Economics Journal aim to shed light on the economic effects of the COVID-19 pandemic by looking at the macro-and microeconomic effects on entrepreneurship and small businesses as well as the role of financial support policies and well-being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 0 publications
0
47
0
2
Order By: Relevance
“…Research by Belitski, Guenther, Kritikos, and Thurik (2022) found that the COVID-19 crisis resulted in more small businesses thinking about entrepreneurship in a new way. Thus, the findings of this study support this view by showing that digital platforms enabled farm entrepreneurs to access required information in a timely manner in order to capitalise on business opportunities.…”
Section: Discussion: Development Of a Conceptual Frameworkmentioning
confidence: 99%
“…Research by Belitski, Guenther, Kritikos, and Thurik (2022) found that the COVID-19 crisis resulted in more small businesses thinking about entrepreneurship in a new way. Thus, the findings of this study support this view by showing that digital platforms enabled farm entrepreneurs to access required information in a timely manner in order to capitalise on business opportunities.…”
Section: Discussion: Development Of a Conceptual Frameworkmentioning
confidence: 99%
“…Fiscal economic reforms, including financial reforms on long-term spending, improved healthcare outcomes, increased life satisfaction, and increased government trust [ 30 ]. The current literature is related to the vulnerability of the coronavirus to different sectors, including renewable energy [ 31 ], higher education [ 32 ], environmental quality [ 33 ], public health [ 34 ], SMEs [ 35 ], and the stock return of pharmaceutical companies [ 36 ]. These studies, in general, concluded that economic activity was mainly depressed during the wake of the COVID-19 pandemic; hence, it is imperative to minimize coronavirus cases to support growth-driven activities worldwide.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As a result, SMEs had difficulties in repaying loans and interest (Lu et al 2020 ; Robinson and Kengatharan 2020 ) placing unprecedented pressures on operations of many SMEs. These impacts are not uniform across the vast diversity of small firms, however, with construction, hospitality and the arts facing some of the most serious declines (Belitski et al 2022 ; Fairlie 2020 ).…”
Section: Sustainable Smes’ Contributions To Building Resilient Pathwaysmentioning
confidence: 99%